Duplex US acquisition and analysis protocol for portal hypertension: a technical note - Mauricio Figueroa-Sanchez; Aldo A. Montero-Cedeño; Guillermo Subias-Rodriguez (Journal of the Mexican Federation of Radiology and Imaging)
Duplex ultrasound (US) is a useful non-invasive imaging modality with high specificity and moderate sensitivity for assessing portal hypertension. Liver cirrhosis is the most common cause of portal hypertension, accounting for 90% of all causes. Portal hypertension can cause complications such as variceal bleeding, ascites, and hepatic encephalopathy. A comprehensive duplex US acquisition and analysis protocol for portal hypertension, as well as its usefulness for evaluation, etiology, and anatomic location, has not been established. This technical note proposes a comprehensive duplex US protocol for portal hypertension that uses a vascular preset of the abdomen and liver and morphologic and hemodynamic assessment of five regions in sequential order: splenic, pancreatic, cardiac, hepatic, and inframesocolic. Morphological parameters include dimension, volume, echotexture, echogenicity, and the presence of lesions. Hemodynamic parameters include vessel diameter, flow direction, spectral morphology, flow velocity, the presence of thrombi, resistance index (RI), and pulsatility index (PI). In the liver, the assessment includes atrophy or hypertrophy, regenerative nodules, and the surface pattern. Hepatic and splenic elastography are recommended as complementary examinations. This technical note, which includes all available duplex US modalities, such as grayscale, color Doppler, power Doppler, and B-Flow examinations, is published for educational purposes.